Does adding a root replacement in type A aortic dissection repair provide better outcomes?. Issue 12 (16th September 2020) - Munir, Wahaj; Harky, Amer; Bashir, Mohamad; Adams, Benjamin
Abstract: Background: Acute type A aortic dissection (ATAAD), is a surgical emergency often requiring intervention on the aortic root. There is much controversy regarding root management; aggressively pursuing a root replacement, versus more conservative approaches to preserve native structures. Methods: Electronic database search we performed through PubMed, Embase, SCOPUS, google scholar, and Cochrane identifying studies that reported on outcomes of surgical repair of ATAAD through either root preservation or replacement. The identified articles focused on short‐ and long‐term mortalities, and rates of reoperation on the aortic root. Results: There remains controversy on replacing or preserving aortic root in ATAAD. Current evidence supports practice of both trends following an extensive decision‐making framework, with conflicting series suggesting favorable results with both procedures as the approach that best defines higher survival rates and lower perioperative complications. Yet, the decision to perform either approach remains surgeon decision and bound to the extent of the dissection and tear entries in strong correlation with status of the aortic valve and involvement of coronaries in the dissection. Conclusions: There exists much controversy regarding fate of the aortic root in ATAAD. There are conflicting studies for impact of root replacement on mortality, whilst some study's report no significant results at all. There is strong evidence regarding risk of reoperation being greater when root is not replaced. Majority of these studies are limited by the single centered, retrospective nature of these small sample sized cohorts, further hindered by potential of treatment bias.